PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN DI COAL MINING DEPARTMEN PT KALTIM PRIMA COAL SANGATTA - KUTAI TIMUR - Alamsyah, Firman (EKONOMIA, 2013)
Firman Alamsyah , Faculty of Economics, University of Samarinda August 17, 1945 " Effect of Incentives on Employee Performance in Coal Mining Department PT . Kaltim Prima Coal Sengata " .Work incentives is a tribute in the form of money given by companies to employees so that they work with high motivation and achievement in achieving corporate goals .Employee Incentive Scheme PT . KPC 2010 has been approved by shareholders and are happy that the incentives are available for 2010 may reach 600 % of base salary or more if some production targets are met , employees come to work regularly and work safely . Payable on a quarterly basis , the number can reach 150 % of basic salary for each kwartalnya , Improvement of such a large number of incentives in 2010 reflects the philosophy of the new shareholders to give a larger share to the employees motivatedThe hypothesis that the writer can convey is suspected Are Incentives significant effect on the Effect of Incentives on Employee Performance in Coal Mining Department PT . Kaltim Prima Coal Sangatta , development can be seen the number of working hours (working hours ) of January 2009 through the end of June 2012 continues to increase .The analysis showed that the average ratio of employees of PT growth incentives . Kaltim Prima Coal dive outside banks of 2009 to second quarter of 2012 by using a uniform unit of measurement is used , then used the formula ( the formula ) , namely : ( tn - t n - 1 ) : t n - 1 with a unit of measurement percentage ( % ) . The results of the analysis of the growth of the quarter amounted to 10.21 % . The highest growth of 84.17 % incentive in the fourth quarter of 2010 - I 2011 . While incentives lowest growth in the first quarter - II 2003 amounted to -7.95 % . Average growth ratio of working hours of employees on Coal Mining Department PT . KPC Sangatta during the first quarter of 2009 - II 2012 is 4.73 % , the highest achieved growth in hours worked was 46.93 % in the fourth quarter of 2011 - the first of 2012, while the lowest pertumbuahn working hours amounted to -7.95 % in the first quarter - II in 2011 . By using linear regression analysis method , Y = a + bX , the value of the regression coefficient incentive variable ( X ) is equal to 0.248 , 0.885 and its constant is then obtained by the following linear regression equation : Y = 0.248 + 0.885 X. In the above can be interpreted any changes to variable incentives ( X ) has a positive effect on the impact of changes in working hours . The results of the analysis of the standardized coefficient incentive variable ( X ) is equal to 0.860 of the value of the standardized variables above, it can be stated that the response variable incentives have a positive effect on working hours / working spirit . Based on the above explanation , the hypothesis stated that incentives significantly influence employee morale in Heavy Equipment Maintenance PT . Kaltim Prima Coal Sengata is correct and acceptable .Â